Paul Robeson - Horne, Gerald (Pluto Press, 2016)
A world-famous singer and actor, a trained lawyer, an early star of American professional football and a polyglot who spoke over a dozen languages. These could be the crowning achievements of a life well-lived, yet for Paul Robeson the higher calling of social justice led him to abandon both the NFL and Hollywood and become one of the most important political activists of his generation - battling both Jim Crow and Joseph McCarthy. Gerald Horne's new biography uses Robeson's remarkable and revolutionary life to tell the story of the 20th Century's great political struggles: against racism, against colonialism, and for international socialism. This critical and searching account provides an opportunity for readers to comprehend the triumphs and tragedies of the revolutionary progressive movement of which he was not just a part, but, perhaps, its most resonant symbol.